High-resolution spectral and anisotropy characteristics of solar protons during the GLE N°73 on 28 October 2021 derived with neutron-monitor data analysis - Mishev, A. L. (Alexander L.); Kocharov, L. G. (Leon G.); Koldobskiy, S. A. (Sergey A.); Larsen, N. (Nicholas); Riihonen, E. (Esa); Vainio, R. (Rami); Usoskin, I. G. (Ilya G.) (Springer Nature, 2022)
Abstract The first ground-level enhancement of the current Solar Cycle 25 occurred on 28 October 2021. It was observed by several space-borne and ground-based instruments, specifically neutron monitors. A moderate count-rate increase over the background was observed by high-altitude polar stations on the South Pole and Dome C stations at the Antarctic plateau. Most of the neutron monitors registered only marginal count-rate increases. Using detrended records and employing a method verified by direct space-borne measurements, we derive the rigidity spectra and angular distributions of the incoming solar protons in the vicinity of Earth. For the analysis, we employed a newly computed and parameterized neutron-monitor yield function. The rigidity spectra and anisotropy of solar protons were obtained in their time evolution throughout the event. A comparison with the Solar and Heliospheric Observatory/Energetic and Relativistic Nuclei and Electron (SOHO/ENRE) experiment data is also performed. We briefly discuss the results derived from our analysis.